2020
DOI: 10.1186/s12877-020-1455-x
|View full text |Cite
|
Sign up to set email alerts
|

The care capacity goals of family carers and the role of technology in achieving them

Abstract: Background: As global populations age, governments have come to rely heavily on family carers (FCs) to care for older adults and reduce the demands made of formal health and social care systems. Under increasing pressure, sustainability of FC's unpaid care work has become a pressing issue. Using qualitative data, this paper explores FCs' care-related work goals, and describes how those goals do, or do not, link to technology. Methods: We employed a sequential mixed-method approach using focus groups followed b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 76 publications
2
21
0
1
Order By: Relevance
“…This differs from the previous dimension in that it focuses on the ICs’ awareness that they are not alone in the caregiving situation, especially in emergencies, whereas in the previous dimension, the focus was on ensuring the care recipient’s safety. Many studies have reported on the importance of a safety net that enables ICs to continue to care for an care recipient at home [ 57 , 58 ]. A safety net could be provided by various support resources and services, ranging from family and community support (e.g., friends, neighbors) to privately paid assistants and formal services, including new technologies, such as telecare systems [ 35 , 36 , 57 , 58 , 59 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…This differs from the previous dimension in that it focuses on the ICs’ awareness that they are not alone in the caregiving situation, especially in emergencies, whereas in the previous dimension, the focus was on ensuring the care recipient’s safety. Many studies have reported on the importance of a safety net that enables ICs to continue to care for an care recipient at home [ 57 , 58 ]. A safety net could be provided by various support resources and services, ranging from family and community support (e.g., friends, neighbors) to privately paid assistants and formal services, including new technologies, such as telecare systems [ 35 , 36 , 57 , 58 , 59 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our co-creation approach was rooted in the belief that the population of interest (ie, family caregivers) are equal stakeholders and contributors throughout the research project. 21 Caregivers and organizations that represent them were involved in developing and beta-testing the survey instrument and recruiting a broad range of caregivers in Canada to complete the survey. Through this co-creation process with family caregivers, we learned that the concept of goals better represents what family caregivers seek to help them integrate their care work with other life responsibilities (such as raising children and maintaining paid employment).…”
Section: Methodsmentioning
confidence: 99%
“…20 The added time and effort required to navigate these complex systems is yet another item on many family caregivers' growing lists of roles and responsibilities. 21…”
Section: Introductionmentioning
confidence: 99%
“…En esta dimensión se destaca la importancia de poseer conocimiento, habilidades, destrezas y actitudes que definen el desempeño de los cuidadores, las cuales son efectivas para promover conductas deseables entre el cuidador, el receptor de cuidado y la familia, como la socialización, la mejora de la comunicación y la toma efectiva de decisiones. Al respecto, Leslie et al (2020) comentan que para mejorar la capacidad de cuidar será necesario identificar los conocimientos previos relacionados a la condición cambiante de las personas so-bre las que se ejerce el cuidado, un entrenamiento en la navegación y uso de los sistemas de apoyo existentes y, finalmente, ayudar a los CPI a desarrollar estrategias de afrontamiento, así como, oportunidades de tutoría y socialización con otros.…”
Section: Práctica Instrumental O Intervención Terapéuticaunclassified